Two-phase coexisting manganese oxide as well as preparation method and application thereof

By treating the manganese oxides that form the coexisting phases of MnO2/Mn3O4 on the conductive substrate, the problems of insufficient electrocatalyst activity and scarcity of precious metal catalysts at low pH are solved, and high-efficiency water oxidation reaction within the entire pH range is achieved.

CN119898857AActive Publication Date: 2025-04-29HUAZHONG NORMAL UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202410972936.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-19
Publication Date
2025-04-29
Estimated Expiration
2044-07-19

AI Technical Summary

Technical Problem

In the prior art, high-performance redox electrocatalysts at low pH values ​​are difficult to achieve high current density, and precious metal catalysts have scarcity and corrosion problems, making it difficult to operate stably within the entire pH range.

Method used

The manganese oxide coexisting between MnO2/Mn3O4 phases is used to form a cluster-like morphology of nanoparticles accumulation by stirring and heating on the conductive substrate, and the high-water oxidative active Mn3+ components are introduced simultaneously to improve catalytic activity and stability.

Benefits of technology

It achieved excellent catalytic activity and stability in the full pH range (pH 0-14), with significantly reduced OER overpotentials below 10 mAcm-2 and no significant attenuation during long runs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004953747170000071
    Figure BDA0004953747170000071
  • Figure HDA0004953747180000011
    Figure HDA0004953747180000011
  • Figure HDA0004953747180000012
    Figure HDA0004953747180000012
Patent Text Reader

Abstract

The invention discloses a two-phase coexisting manganese oxide, which is a MnO2 / Mn3O4 mixed-phase manganese oxide grown on a substrate, and the MnO2 / Mn3O4 mixed-phase manganese oxide is in a cluster-shaped morphology formed by accumulation of nanoparticles. The preparation method comprises the following steps: adding bromine salt and water into a reaction container, stirring in air, adding manganese salt, and uniformly mixing; and dropwise adding the obtained mixed solution on a substrate quantitatively, and carrying out one-step heating reaction in air to prepare the MnO2 / Mn3O4 two-phase coexisting manganese oxide. When the two-phase coexisting manganese oxide is used as a water oxidation electrode, the two-phase coexisting manganese oxide can show excellent catalytic activity and stability in a full pH range; the preparation method is simple, convenient to operate and suitable for popularization and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of water oxidation catalysts, and in particular relates to a two-phase coexistence manganese oxide suitable for a full pH range, and a preparation method and application thereof. Background Art

[0002] As a secondary energy source, hydrogen has the advantages of diverse sources, cleanliness, high efficiency, sustainable utilization, and wide range of uses. It is of great significance to ensure energy security and address climate change. It is an ideal carrier to promote the large-scale utilization of renewable energy and an important boost to achieve green and low-carbon energy transformation. Among them, hydrogen production by water electrolysis is the main way to prepare "green hydrogen" in the future. In order to be suitable for various application scenarios, electrocatalysts must be able to perform well in a wide pH range to adapt to different proton concentrations in the electrocatalytic process. Many transition metal-based electrocatalysts perform well in concentrated alkaline electrolytes (pH greater than 13), but are prone to corrosive decomposition under low pH working conditions.

[0003] RuO2 and IrO2 are well-known high-performance OER electrocatalysts at low pH, although these catalysts have a low performance at 10 mA cm -2 Although it has a low overpotential at low current density, it has problems such as insufficient exposure of active sites and slow mass and charge transfer, making it difficult to achieve high current density. In addition, due to the release of O2 bubbles, oxidation and corrosion at high potentials, and stripping, the catalytic electrode cannot operate stably for a long time. At the same time, RuO2 and IrO2 are both scarce precious metal materials, making them difficult to commercialize on a large scale.

[0004] Among transition metal-based non-noble metal oxides, manganese oxide (MnO x ) has rich valence states and crystal structures, and exhibits excellent performance in various electrochemical reactions. Manganese oxides can act as efficient bifunctional electrocatalysts for ORR and OER under alkaline conditions; some manganese-based oxides can be used as OER catalysts in acidic media, but most of the reported catalytic activities are very limited, below 10 mA cm -2 The overpotential under low pH is usually greater than 500 mV, which makes it difficult to apply commercially. It is necessary to further improve the OER activity of this type of manganese-based materials in low pH environments. Summary of the invention

[0005] The main purpose of the present invention is to provide a manganese oxide in which MnO2 and Mn3O4 coexist in two phases (referred to as two-phase manganese oxide) in order to solve the problems and shortcomings of the prior art, and to simultaneously introduce a high water oxidation active Mn into the catalyst. 3+The nanoparticle structure constructed at the same time can achieve a large specific surface area, so that it can be used as a water oxidation electrode in the entire pH range, showing excellent catalytic activity and stability; and the preparation method involved is relatively simple and easy to operate, which is suitable for popularization and application.

[0006] To achieve the above object, the technical solution adopted by the present invention is:

[0007] A two-phase coexisting manganese oxide is a MnO2 / Mn3O4 mixed phase manganese oxide grown on a substrate, wherein the atomic percentage of Mn is 25.09-52.05%, and the atomic percentage of O is 47.95-74.91%.

[0008] Furthermore, the MnO2 / Mn3O4 mixed-phase manganese oxide has a clustered morphology formed by accumulation of nanoparticles, and the size of the nanoparticles is 20 to 80 nm.

[0009] Furthermore, the substrate is a conductive substrate.

[0010] The above-mentioned method for preparing a two-phase coexisting manganese oxide comprises the following steps: adding bromine salt and water into a reaction container, stirring them under air, and then adding manganese salt to mix them evenly; then quantitatively dropping the obtained mixed solution on a substrate, and performing a one-step heating reaction in air to obtain MnO 2 / Manganese oxide in which two phases of Mn3O4 coexist.

[0011] In the above scheme, the stirring treatment time is 3 to 6 hours.

[0012] In the above scheme, the substrate is preferably a conductive substrate, specifically including any one of carbon cloth, carbon paper, graphite felt, carbon fiber, bio-carbon material and the like.

[0013] Furthermore, the biocarbon material can be a carbon material obtained by calcining fruit shells or mollusk shells.

[0014] In the above scheme, the manganese salt includes one or more of Mn(NO3)2, MnSO4, MnCl2, etc.

[0015] In the above scheme, the bromine salt includes one or more of NH4Br, NaBr, and KBr.

[0016] In the above scheme, in the mixed solution, the mass concentration of manganese salt is 20-60%, and the concentration of bromine salt is 0.1-2.0 mol / L.

[0017] In the above scheme, the heating reaction temperature in air is 150-400° C. and the time is 2-12 hours.

[0018] Furthermore, the heating reaction adopts a heating rate of 5-25°C / min.

[0019] The present invention also provides an application of the two-phase coexisting manganese oxide in water oxidation reaction in a full pH range.

[0020] Furthermore, the full pH range is pH values ​​0-14.

[0021] Furthermore, the specific application method includes: using the two-phase coexisting manganese oxide as an oxygen evolution electrode for the oxidation reaction of acidic water, neutral water, and alkaline water.

[0022] The two-phase coexistence manganese oxide of the present invention is used to generate a -2 At current densities of 10 mA cm-2, the OER overpotentials required in acidic, neutral, and alkaline media are as low as 255, 267, and 175 mV, which is much lower than that of pure MnO2 samples. -2 It can operate stably for more than 500 hours in acidic, neutral and alkaline solutions at a constant current density, and its water oxidation performance has no obvious attenuation.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] 1. The present invention firstly stirs the bromine salt solution, then mixes it with the manganese salt and heats it in one step, and prepares the two-phase coexisting manganese oxide on a substrate, preferably a conductive substrate such as a conductive carbon material; wherein the stirring step first oxidizes the bromine salt in the air to Br - and liquid bromine coexistence system, and then under air and heating conditions, Mn 2+ Directly oxidized to form Mn-containing 3+ The obtained two-phase manganese oxide has a cluster-like morphology formed by the accumulation of nanoparticles, which can fully expose the active sites. At the same time, the formation of Mn3O4 increases the Mn with high OER activity. 3+ The species content and the combined effect of various means can effectively improve the catalytic activity and stability of the obtained manganese oxide and effectively broaden its pH value application range;

[0025] 2. The two-phase manganese oxide provided by the present invention is used as an OER electrode, which can show excellent catalytic activity and stability in the entire pH range (pH 0 to 14), and can provide a new idea for the preparation of high-performance water oxidation catalysts;

[0026] 3. The preparation method involved in the present invention is relatively simple, easy to operate, and suitable for popularization and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1XRD spectra of two-phase MnO2 / Mn3O4 and pure MnO2 prepared in Example 1 and Comparative Example 1.

[0028] Figure 2 Scanning electron microscope (SEM) images of the two-phase MnO2 / Mn3O4 and pure MnO2 prepared in Example 1 and Comparative Example 1 at different magnifications.

[0029] Figure 3 The OER performance comparison diagram of the MnO2 / Mn3O4 two-phase manganese oxide obtained in Example 1 in an acidic electrolyte (0.5M H2SO4) with the precious metal IrO2 sample and the products obtained in Comparative Examples 1 to 3, wherein: (a) a linear sweep voltammetry (LSV) curve comparison diagram of the products obtained in Example 1 and Comparative Example 1 and the precious metal IrO2 sample; (b) an electrochemical impedance spectroscopy (EIS); (c) a Faraday efficiency test; (d) a linear sweep voltammetry curve comparison diagram of Example 1 and Comparative Examples 1 to 3; (e) a linear sweep voltammetry curve comparison diagram of the product obtained in Example 1 at 10 mA cm -2 Stability test curves under current density and acidic conditions.

[0030] Figure 4 The OER performance comparison diagram of the MnO2 / Mn3O4 two-phase manganese oxide obtained in Example 1 in a neutral electrolyte (PBS solution) and the precious metal IrO2 sample: (a) linear sweep voltammetry (LSV) curve; (b) electrochemical impedance spectroscopy (EIS); (c) Faraday efficiency test; (d) at 10 mA cm -2 Stability test curve under current density.

[0031] Figure 5 The OER performance comparison of the MnO2 / Mn3O4 two-phase manganese oxide obtained in Example 1 in alkaline electrolyte (1M KOH) and the commercial precious metal IrO2 sample is shown in the figure: (a) linear sweep voltammetry (LSV) curve; (b) electrochemical impedance spectroscopy (EIS); (c) Faraday efficiency test; (d) at 10 mA cm -2 Performance curve of stable test under current density. DETAILED DESCRIPTION

[0032] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0033] Example 1

[0034] A manganese oxide with coexisting MnO2 / Mn3O phases, the two-phase manganese oxide is grown on a carbon cloth substrate and exhibits a cluster morphology formed by accumulation of nanoparticles; the specific preparation steps are as follows:

[0035] Prepare a 1.6 mol / L NH4Br uniform solution, stir it in air for 5 h, then add Mn(NO3)2 (the concentration of manganese nitrate in the solution is 40 wt%) to the obtained bromine-based solution; -2 A drop amount of the coating was dropped on the treated clean carbon cloth, heated to 250°C on a heating plate at a heating rate of 10° / min, and kept warm for 5.5 hours. After the reaction was completed, it was cooled to room temperature to obtain a two-phase manganese oxide MnO2 / Mn3O4.

[0036] The product obtained in this example was tested by inductively coupled plasma resonance spectroscopy (ICP-OES), and the atomic percentage of Mn was found to be 47.57%, and the atomic percentage of O was 52.43%.

[0037] Example 2

[0038] A manganese oxide with coexisting MnO2 / Mn3O phases, the two-phase manganese oxide is grown on a carbon paper substrate and exhibits a cluster morphology formed by accumulation of nanoparticles; the specific preparation steps are as follows:

[0039] Prepare a 1.0 mol / L NaBr uniform solution, stir it in air for 4 h, then add MnSO4 (the concentration of manganese sulfate in the solution is 50 wt%) to the obtained bromine-based solution; -2 The mixture was dropped onto the clean carbon paper and heated to 300°C at a heating rate of 10°C / min on a hot plate. The mixture was kept warm for 9 hours. After the reaction was completed, the mixture was cooled to room temperature to obtain a two-phase manganese oxide MnO2 / Mn3O4.

[0040] The product obtained in this example was subjected to ICP-OES test, and the atomic percentage of Mn was found to be 39.46%, and the atomic percentage of O was 60.54%.

[0041] Example 3

[0042] A manganese oxide in which two phases of MnO2 / Mn3O coexist, the two-phase manganese oxide grows on a carbon fiber substrate and exhibits a cluster morphology formed by accumulation of nanoparticles; the specific preparation steps are as follows:

[0043] Prepare a 2.0 mol / L NH4Br uniform solution, stir it in air for 6 h, then add MnCl2 (the concentration of manganese chloride in the solution is 60 wt%) to the obtained bromine-based solution; -2A drop amount of the coating is dropped on the treated clean carbon fiber, heated to 400°C on a heating plate at a heating rate of 10°C / min, and kept warm for 12 hours. After the reaction is completed and cooled to room temperature, a two-phase manganese oxide MnO2 / Mn3O4 is obtained.

[0044] The product obtained in this example was subjected to ICP-OES test, and the atomic percentage of Mn was 52.05%, and the atomic percentage of O was 47.95%.

[0045] Example 4

[0046] A manganese oxide with coexisting MnO2 / Mn3O phases, the two-phase manganese oxide is grown on a carbon cloth substrate and exhibits a cluster morphology formed by accumulation of nanoparticles; the specific preparation steps are as follows:

[0047] Prepare a 0.1 mol / L KBr uniform solution, stir it in air for 3 h, then add MnSO4 (the concentration of manganese sulfate in the solution is 20 wt%) to the obtained bromine-based solution; -2 A drop amount of the coating is dropped on the treated clean carbon cloth, and the mixture is heated to 150°C at a heating rate of 10°C / min on a heating plate. The reaction is carried out for 2 hours. After the reaction is completed, the mixture is cooled to room temperature to obtain a two-phase manganese oxide MnO2 / Mn3O4.

[0048] The product obtained in this example was subjected to ICP-OES test, and the atomic percentage of Mn was found to be 25.09%, and the atomic percentage of O was 74.91%.

[0049] Example 5

[0050] A manganese oxide with coexistence of two phases of MnO2 / Mn3O, the two-phase manganese oxide is grown on a graphite felt substrate and exhibits a cluster morphology formed by accumulation of nanoparticles; the specific preparation steps are as follows:

[0051] Prepare a 0.5 mol / L KBr uniform solution, stir it in air for 5 h, then add Mn(MO3)2 (the concentration of manganese nitrate in the solution is 30 wt%) to the obtained bromine-based solution; -2 A drop amount of the coating is dropped on the cleaned graphite felt, and the mixture is heated to 200°C on a heating plate at a heating rate of 10°C / min. The mixture is kept warm for 4 hours. After the reaction is completed, the mixture is cooled to room temperature to obtain a two-phase manganese oxide MnO2 / Mn3O4.

[0052] The product obtained in this example was subjected to ICP-OES test, and the atomic percentage of Mn was found to be 31.98%, and the atomic percentage of O was 68.02%.

[0053] Comparative Example 1

[0054] A pure phase MnO2 electrocatalyst, the preparation method of which comprises the following steps:

[0055] The carbon cloth was soaked in concentrated nitric acid, ultrasonically cleaned three times with deionized water, and then ultrasonically cleaned three times with anhydrous ethanol. A 40% manganese nitrate solution was added at 150 uL cm -2 A drop amount of the coating was dropped on a clean carbon cloth, heated to 250°C on a heating plate at a heating rate of 10°C / min, and reacted for 5.5 hours. After the reaction was completed, it was cooled to room temperature to obtain pure phase manganese oxide MnO2.

[0056] Comparative Example 2

[0057] A method for preparing manganese oxide induced by chloride salt comprises the following steps:

[0058] Prepare a 1.6 mol / L NH4Cl uniform solution, stir it in air for 5 h, then add Mn(NO3)2 (the concentration of manganese nitrate in the solution is 40 wt%) to the obtained bromine-based solution; -2 A drop amount of the coating was dropped on the treated clean carbon cloth, heated to 250°C on a heating plate at a heating rate of 10°C / min, and kept warm for 5.5 hours. After the reaction was completed, it was cooled to room temperature to obtain manganese oxide induced by chloride salt.

[0059] Comparative Example 3

[0060] A manganese oxide directly induced by a bromine salt, the preparation method of which comprises the following steps:

[0061] Prepare a 1.6 mol / L NH4Br uniform solution, then add Mn(NO3)2 (the concentration of manganese nitrate in the solution is 40 wt%) to the solution; -2 A drop amount of the solution was dropped onto the clean carbon cloth, and the solution was heated to 250°C at a heating rate of 10°C / min on a heating plate. The reaction was kept warm for 5.5 hours. After the reaction was completed, the solution was cooled to room temperature to obtain manganese oxide directly induced by bromine salt.

[0062] The pure phase MnO2 and two-phase MnO2 / Mn3O4 prepared in Comparative Example 1 and Example 1 were characterized by XRD. The specific steps were as follows: the prepared catalyst was subjected to X'pert PROMPD X-ray diffractometer (XRD) to determine the crystal structure of the sample under the conditions of Cu Kα monochromatic radiation and a scanning range of 20° to 80°. The obtained XRD spectra are shown in FIG. Figure 1The results show that the characteristic peaks on the pure phase MnO2 XRD spectrum match those of MnO2 (PDF#30-0820), indicating that manganese dioxide was successfully synthesized; after the addition of bromine-containing reagents during the preparation process, some new peaks appeared in the obtained MnO2-based products, which match those of Mn3O4 (PDF#24-0734), indicating that the introduction of bromine can effectively promote the formation of MnO2 and Mn3O4 complexes.

[0063] The pure phase MnO2 and two-phase MnO2 / Mn3O4 prepared in Comparative Example 1 and Example 1 were characterized by SEM. The specific steps were as follows: the surface morphology of the prepared catalyst was measured on a JOELSEM-6700E scanning electron microscope (SEM); the results are shown in Figure 2 It can be seen that the pure MnO2 obtained in Comparative Example 1 exhibits a bulk structure; the product obtained by the preparation method described in Example 1 after the introduction of Br is a cluster structure formed by the accumulation of nanoparticles ( Figure 2 c), can fully expose the active sites.

[0064] The products obtained in Example 1, Comparative Examples 1 to 3, and the noble metal IrO2 sample were respectively tested for the performance of electrocatalytic oxygen evolution reaction. The specific steps are: using the three-electrode system of the CHI660E electrochemical workstation, the Ag / AgCl electrode, the Hg / HgO electrode, and the calomel electrode were used as reference electrodes under acidic, neutral, and alkaline conditions, respectively, the prepared sample was used as the working electrode, the graphite electrode was used as the counter electrode, and the electrolytes were 0.5 mol / L H2SO4 solution (pH 0), PBS solution, and 1 mol / L KOH solution (pH 14), respectively, at room temperature of 25°C. Before the test, cyclic voltammetry scanning was performed on the samples to activate and stabilize the samples. The linear sweep voltammetry (LSV) curve with 90% IR compensation was used to evaluate the activity of the electrode, and the scanning rate was 2mV s -1 The measurement range of the electrochemical impedance spectroscopy (EIS) of the electrode is 1000kHz~0.1Hz. -1The stability of the electrode is tested at a constant current density of . The Faraday efficiency test is obtained by testing in a gas chromatograph. The specific steps are: clean the H-type reactor with deionized water, pour the electrolyte into the cathode chamber and the anode chamber respectively, so that the liquid levels are at the same level, and leave a certain volume of cavity above the inside of the anode chamber to collect oxygen products. High-purity carbon dioxide (99.99%) gas is introduced into the cathode chamber and the anode chamber for 30 minutes respectively to make the electrolyte reach a CO2 saturated state. The sample is then activated, and then the CHI660E electrochemical workstation it mode is selected. Each time the charge reaches a fixed value of 15C, the potential is stopped. Then use a sampling needle (Hamilton) to take out a 500μL gas sample from the headspace of the anode chamber and inject it into the gas chromatograph. The GC-2014 gas chromatograph is used to test the O2 content. The results are shown in Figure 3 ,in, Figure 3 (a) shows the linear sweep voltammetry (LSV) curves of MnO2 / Mn3O4 two-phase manganese oxide and commercial IrO2 samples in 0.5 mol / L H2SO4 solution (pH 0). Compared with other samples, MnO2 / Mn3O4 sample has significantly improved OER performance, at 10 mA cm -2 At a current density of 1.3 Å, the required OER overpotential is only as low as 255 mV, which is better than the commercial IrO2 sample (317 mV). At the same time, the formation of two-phase oxides is also beneficial to improve conductivity, thereby promoting rapid electron transfer on the catalyst, as shown in Figure 3 (b) The electrochemical impedance spectroscopy diagram shows that the MnO2 / Mn3O4 two-phase manganese oxide has the smallest charge transfer resistance. Figure 3 (c) The Faradaic efficiency of the MnO2 / Mn3O4 sample obtained in Example 1 is 98%, demonstrating its good OER selectivity. Figure 3 (d) shows the linear sweep voltammetry (LSV) curves of the samples of Example 1 and Comparative Examples 1-3 in 0.5 mol / L H2SO4 solution. The results show that the products obtained in Comparative Examples 1-3 cannot achieve effective catalytic effect under acidic conditions. In addition, Figure 3 (e) The stability test shows that the MnO2 / Mn3O4 sample obtained in Example 1 has a stable -2 The oxidation performance of the device has not been significantly attenuated after running at a constant current density of 500 hours in an acidic solution.

[0065] Figure 4(a) shows the linear sweep voltammetry (LSV) curves of MnO2 obtained in comparative example 1, MnO2 / Mn3O4 two-phase manganese oxide obtained in example 1, and commercial IrO2 samples in PBS solution (pH 7). Compared with other samples, the MnO2 / Mn3O4 sample obtained in the present invention has significantly improved OER performance, at 10 mA cm -2 At a current density of 1.3 Å, the required OER overpotential is only as low as 267 mV, which is better than the commercial IrO2 sample (432 mV). At the same time, the formation of two-phase oxides is also beneficial to improve conductivity, thereby promoting rapid electron transfer on the catalyst, as shown in Figure 4 (b) The electrochemical impedance spectroscopy diagram shows that the MnO2 / Mn3O4 two-phase manganese oxide has the smallest charge transfer resistance. Figure 4 (c) It can be seen that the Faradaic efficiency of MnO2 / Mn3O4 obtained by the present invention is 96.1%, which proves its good OER selectivity. In addition, Figure 4 (c) The stability test results show that the MnO2 / Mn3O4 sample obtained by the present invention has a stability of 10 mA cm -2 The oxidation performance of the sample did not significantly decay after running for 700 hours at a constant current density in a neutral solution.

[0066] Figure 5 (a) shows the linear sweep voltammetry (LSV) curves of MnO2 obtained in comparative example 1, MnO2 / Mn3O4 two-phase manganese oxide obtained in example 1, and commercial IrO2 samples in 1 mol / L KOH solution (pH 14). Compared with other samples, the MnO2 / Mn3O4 sample has significantly improved OER performance, at 10 mA cm -2 At a current density of 1.5 Å, the required OER overpotential is only as low as 175 mV, which is better than the commercial IrO2 sample (258 mV). At the same time, the formation of two-phase oxides is also beneficial to improve conductivity, thereby promoting rapid electron transfer on the catalyst, as shown in Figure 5 (b) The electrochemical impedance spectroscopy diagram shows that MnO2 / Mn3O4 has the smallest charge transfer resistance. Figure 5 (c) It can be seen that the Faradaic efficiency obtained by the present invention is 93.1%, which proves its good OER principle. Figure 5 (d) shows the stability test results of MnO2 / Mn3O4 samples at 10mAcm -2 The oxidation performance of the device has not been significantly attenuated after running for 500 hours in an alkaline solution at a constant current density of 1.58kcal / s.

[0067] The MnO2 / Mn3O4 two-phase coexisting manganese oxide obtained in Examples 1 to 5 was used to prepare an oxygen evolution electrode. The specific steps were as follows: using a three-electrode system of a CHI660E electrochemical workstation, an Ag / AgCl electrode as a reference electrode, the prepared sample as a working electrode, a graphite electrode as a counter electrode, an electrolyte of 0.5 mol / L H2SO4 solution, and a room temperature of 25°C; different samples were tested at 10 mA cm -2 The overpotentials of acidic water oxidation at current densities of are shown in Table 1.

[0068] Table 1 Summary of the acidic water oxidation performance of MnO2 / Mn3O4 samples prepared in different embodiments

[0069]

[0070] The above embodiments are only examples for clear explanation, and are not intended to limit the implementation methods. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here, so the obvious changes or modifications derived are still within the protection scope of the invention.

Claims

1. A two-phase coexisting manganese oxide, characterized in that: It is a MnO2 / Mn3O4 mixed phase manganese oxide grown on a substrate, wherein the atomic percentage of Mn is 25.09-52.05%, and the atomic percentage of O is 47.95-74.91%.

2. The two-phase coexisting manganese oxide according to claim 1, characterized in that: The MnO2 / Mn3O4 mixed phase manganese oxide is in a clustered morphology formed by accumulation of nanoparticles, and the size of the nanoparticles is 20 to 80 nm.

3. The method for preparing the two-phase coexisting manganese oxide according to claim 1, characterized in that: The method comprises the following steps: adding bromine salt and water into a reaction container, stirring the mixture in air, and then adding manganese salt and mixing the mixture evenly; then dropping the mixture on a substrate in a quantitative manner, and performing a one-step heating reaction in air to obtain MnO 2 / Manganese oxide in which two phases of Mn3O4 coexist.

4. The preparation method according to claim 3, characterized in that: The stirring treatment time is 3 to 6 hours.

5. The preparation method according to claim 3, characterized in that: The substrate includes any one of carbon cloth, carbon paper, graphite felt, carbon fiber, and biocarbon material.

6. The preparation method according to claim 3, characterized in that: The manganese salt includes one or more of Mn(NO3)2, MnSO4, and MnCl2; the bromine salt includes one or more of NH4Br, NaBr, and KBr.

7. The preparation method according to claim 3, characterized in that: In the obtained mixed solution, the mass concentration of manganese salt is 20-60%, and the concentration of bromine salt is 0.1-2.0 mol / L.

8. The preparation method according to claim 3, characterized in that: The heating reaction temperature in air is 150-400°C and the time is 2-12 hours.

9. Use of the two-phase coexisting manganese oxide according to any one of claims 1 to 2 or the two-phase coexisting manganese oxide prepared by the preparation method according to any one of claims 3 to 8 in a water oxidation reaction.

10. The use according to claim 9, characterized in that: The pH value in the water oxidation reaction is 0-14.

Citation Information

Patent Citations

  • Manganese dioxide-manganese tetroxide composite material, preparation method and application thereof

    CN108963234A

  • K-doped alpha-MnO2 / Mn3O4 efficient photothermal catalyst, and preparation method and application thereof

    CN110102290A

  • Manganese oxide for water decomposition catalysts, manganese oxide-carbon mixture, manganese oxide composite electrode material, and respective methods for producing these materials

    CN111465581A

  • Manganese oxide nanostructure electrode material and preparation method and application thereof

    CN111986931A

  • Non-noble metal-based acidic electrolytic water oxygen evolution reaction electrocatalyst and preparation method thereof

    CN114540864A